FAKTOR YANG MEMPENGARUHI KEJADIAN HIPERTENSI PADA PEKERJA NELAYAN DI WILAYAH KERJA PUSKESMAS MUARA SABAK TIMUR TANJUNG JABUNG TIMUR TAHUN 2022 - Rafika Duri; T Samsul Hilal (Bajang Institute, 2024)
One of the occupational risks of fishermen is hypertension. Long working hours, heavy physical activity and irregular rest periods have the potential to cause hypertension in fishermen. The percentage of hypertension in fishermen in the East Muara Sabak Health Center working area is 58.7%. This study aims to determine the factors that influence the incidence of hypertension in fishermen workers in the East Muara Sabak Health Center working area. The research design used was cross sectional. The sample in the study were fishermen in the work area of the East Muara Sabak Health Center as many as 43 workers. The sampling technique was total sampling. This research was conducted from November to December 2021. The research instrument was a questionnaire. The statistical tests used were the chi square test. The results of the study were 28, 60.6% of respondents suffered from hypertension, the average working period of respondents was 12.568 years, 60.5% of respondents consumed coffee, 53.5% of respondents experienced severe category work stress and the average length of work of respondents was 5.86 hours / day. The results of bivariate analysis showed that there was an association between coffee consumption (p=0.041), work stress (p=0.000) with the incidence of hypertension. There is no relationship between smoking (p=0.176) and length of work (p=0.148) with the incidence of hypertension. Hypertension in fishermen in the Muara Sabak Timur Health Center working area is related to coffee consumption with work stress, so it is hoped that fishermen will carry out stress management such as implementing a healthy lifestyle such as doing sports (walking leisurely) by doing exercise, the muscles of the body will relax and improve mood. In addition, to reduce coffee consumption.